Demographic, Clinical, and Service Utilization Factors Associated with Suicide‐Related Visits among Alaska Native and American Indian Adults. Issue 1 (25th April 2016) - Dillard, Denise A.; Avey, Jaedon P.; Robinson, Renee F.; Smith, Julia J.; Beals, Janette; Manson, Spero M.; Comtois, Katherine Anne
Abstract : Alaska Native and American Indian people (AN/AIs) are disproportionately affected by suicide. Within a large AN/AI health service organization, demographic, clinical, and service utilization factors were compared between those with a suicide‐related health visit and those without. Cases had higher odds of a behavioral health diagnosis, treatment for an injury, behavioral health specialty care visits, and opioid medication dispensation in the year prior to a suicide‐related visit compared to gender‐, age‐, and residence‐ (urban versus rural) matched controls. Odds of a suicide‐related visit were lower among those with private insurance and those with non‐primary care ambulatory clinic visits.